Analisis Kesalahan Berbahasa pada Teks Laporan Penelitian Berdasarkan Pedoman Umum Ejaan Bahasa Indonesia (PUEBI) - Khairunissa Khairunissa; Grace Shintia Ori Simamora; Elsa Yolanda Simanjuntak; Domma Wati Klara Sitinjak; Valentina Angel Cristiani Sinaga (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes language errors in research report texts based on the General Guidelines for Indonesian Spelling (PUEBI). The three research report texts analyzed come from scientific journals published in 2024, namely: (1)